Investigação do desenvolvimento microestrutural de eletrólito sólido β/β’’-alumina visando sua utilização em bateria ZEBRA - Rodrigues, Daisy Catharina (2014)
The ZEBRA battery (Zero Emission Battery Research Activity) is an efficient electrochemical energy storage device with high energy density and high power. This has been considered one of the key technologies for insertion into the economic market of electric vehicles and for stationary energy applications. However, due to high internal resistance of this device causes an intense search for new materials for the reduction of this issue. Na-β -alumina solid electrolytes, due to its high ionic conductivity for sodium ions, are among the most promising oxide ionic conductors for the ZEBRA battery, operating at temperatures of approximately 300 ºC, with high efficiency. However, the greatest difficulty in using Na-β -alumina is related to the instability of this phase at higher sintering temperatures, in excess of 1300 ºC. The critical point of this electrolyte is the ceramic processing, which can influence the final mechanical and electrical properties of the material. In this work, the focus was to balance the mechanical and electrical properties through the reduction of microstructure defects, using processed powders with different raw materials and sintering conditions. The microstructure, electric conductivity and mechanical strength of Na-β -alumina samples were evaluated, produced by changing the sodium (Na2CO3 or NaNO3), lithium (LiNO3 or LiAl5O8) and aluminum source (AlO(OH) or Al2O3). The microstructure, and consequently the electric conductivity and mechanical strength were dependent on the type of raw materials and sintering profile. Electrical conductivity of 10-1 S.cm-1 at 300 °C and fracture strength of ~ 111 MPa were obtained after the processing variables improvement have been reached. These values are in full agreement with data available in the literature.